Thermal Conductivity of Al2O3 Nanofluid Utilizing Cross-linked Polyacrylic Acid (PAA) as the Base Fluid: An Experimental Study - Roslinda Fauzi; Rusli Daik; Basirah Fauzi; Siti Nur Liyana Mamauod (BioResources)
The thermal conductivity was measured for Al2O3 nanofluid using a newly developed polymeric base fluid. The novel base fluid of cross-linked polyacrylic acid (PAA) solutions was synthesized via radical polymerization using a distinct deep eutectic solvent (DES). Five weight concentrations of Al2O3 nanoparticles, 0.05, 0.10, 0.15, 0.20, and 0.25 wt%, were dispersed in the polymeric fluid via two dispersing techniques. In the first step, the nanoparticles were stirred using magnetic stirring for 1 h, followed by the sonication technique for another hour to ensure the nanoparticles were well suspended in the base fluid. A KD2 Pro thermal analyzer measured the thermal conductivity of each concentration for the temperature from 30 to 70 °C. The experimental data demonstrated a correlation between thermal conductivity and nanoparticle weight fraction. The results showed that the thermal conductivity increased with the increment of Al2O3 concentration for all set temperatures. The study revealed that the polymeric base fluid could replace the conventional base fluid since the thermal conductivity results were comparable with those reported in the literature.